Los seis ciegos y el elefante - Backstein, Karen; Mitra, Annie (New York : Scholastic, 1999)
Recuenta la fabula de India de seis ciegos que con tocar solamente parte de un elefante se quedan con una comprension incompleta de lo que es.
A retelling of the fable from India about six blind men who each get a limited understanding of what an elephant is by feeling only one part of it.
Translation of: The blind men and the elephant.
"Mariposa, Scholastic en espanol"--P. [4] of cover.
"Grados 1 & 2."--Cover.
Keywords: Folklore -- India; Elephants -- Folklore; Fables